Pembudayaan usahawan dalam Islam: teori dan aplikasi - Abdul Hamid, Solahuddin; Ahmad, Kamarudin (Islamic Business School, 2016)
Scholars agree, entrepreneur personalities such as confident, hardworking, dare to try, motivated and eager to autonomy are universal in nature, which transcends racial, cultural, or geographical limitations.However, if this professional career is associated with Islam, all their behavior should be done in a holistic manner based on the Islamic guidelines. This article focuses on the entrepreneurial acculturation in Islam. Explanation of acculturation is based on standards set by the Quran and Hadith and Islamic intellectual thoughts.The philosophy of Islamic entrepreneurial is based on Rabbani as implementation activities are also part of the Islamic Shari'a.Thus, Islamic entrepreneur personality not only contains the dynamic and competent features, but also emphasizes the integration with spiritual elements.